Editorial - Editor (Dev Sanskriti: Interdisciplinary International Journal, 2022)
A mental disorder is characterized by a clinically significant disturbance in an individual’s cognition, emotional regulation, or behaviour. A World Health Organization’s study conducted in 2019 revealed that one in every eight people, or total 970 million people around the world were living with a mental disorder, with which anxiety and depressive disorders were the most common; while in the year 2020 because of the COVID-19 pandemic, the number of people living with anxiety and depressive disorders rose significantly to 28%. In Allopathic medicine, the main approach of treatment is still drug dependent and have sever lacuna for reversal of normal behaviour, leading a door of psychosomatic approaches than somatopsychic approaches.